2002
DOI: 10.1258/jrsm.95.6.290
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subdural haematoma in the elderly--a North Wales experience

Abstract: Chronic subdural haematoma (CSDH) is predominantly a disease of the elderly. Most of the existing data come from studies done several decades ago. We examined the incidence, risk factors, clinical presentation, management and outcome in elderly patients with CSDH by retrospective study of the period 1996-1999 in the three district hospitals of North Wales. 40 cases of CSDH were identified in patients >65 years, the incidence in this population being 8.2/100,000. Falls (57%) and antithrombotic therapy (33%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 6 publications
5
61
0
2
Order By: Relevance
“…The incidence of cSDH increases greatly with age and ranges from approximately 3.4 per 100,000 in patients younger than 65 years of age, to 8 to 58 per 100,000 in those older than 65 years [4,7,12]. This age dependence is particularly relevant, as the latter population accounted for 35.9 million people in the United States or 12% of the overall population in 2003 [34], a number which is projected to rise to 72 million people (an estimated 20% of the overall population) by the year 2030 [34].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cSDH increases greatly with age and ranges from approximately 3.4 per 100,000 in patients younger than 65 years of age, to 8 to 58 per 100,000 in those older than 65 years [4,7,12]. This age dependence is particularly relevant, as the latter population accounted for 35.9 million people in the United States or 12% of the overall population in 2003 [34], a number which is projected to rise to 72 million people (an estimated 20% of the overall population) by the year 2030 [34].…”
Section: Introductionmentioning
confidence: 99%
“…In 1657, J. J. Wepfer was the first to describe a CSDH, and in 1857, Virchow detailed the pathophysiology of this hematoma, naming it pachymeningitis haemorrhagica interna [1,7]. Many authors have since demonstrated that lesions are easily treated with minimal morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs, which are used in a large proportion of the elderly population, may add to the risk of CSDH by as much as 42.5 times [19]. Some studies report that patients initially taking anticoagulant medications have more risk of recurrence and longer stays in the hospital [2,3,7,13,15,20]. Our results show only 3.5% of all CSDH patients admitted were chronically anticoagulated/antiaggregated or had coagulopathy history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly age dependent, with a 10-fold increase in patients aged >65 years (weighted average 0.026% per patient-year) [28,29,30]. Oral anticoagulants increase the risk by at least another 10-fold to 0.22-0.39% per patient-year, depending mainly on the level of the INR [31,32].…”
Section: Discussionmentioning
confidence: 99%